أبعاد جودة الخدمة وأثرها على ولاء الزبائن وفق نموذج الأداء الفعلي للخدمة - مداني، شريف عبدالله; حمزة زكرياء ،محي الدين; جلام ،كريمة (University of Eloued جامعة الوادي, 2025)
This study aims to try to know the level of service quality provided by Ooredoo and the degree of its impact on customer loyalty, depending on the actual performance model Servperf attributed to (Cronin & Taylor) which focuses on five dimensions (tangibility, reliability, responsiveness, security and empathy) to measure service quality performance. The study was conducted on a sample of Ooredoo customers, the size of which is 117 customers. The questionnaire tool was used to reach the study sample and know their attitudes towards the services provided by Ooredoo and the degree of their loyalty towards the latter. Using the SPSS-23 program, the data obtained from the study sample was analyzed with the help of various statistical methods. The study results showed a positive correlation between Ooredoo's service quality and customer loyalty. We observed a positive impact of the responsiveness dimension on customer loyalty, while the other dimensions (tangibility, reliability, responsiveness, assurance, and empathy) had a weak impact and did not meet customer expectations.
Dimensions of service quality and its impact on customer loyalty according to the actual service performance model (Servperf) - a study of a sample of -Ooredoo customers -Algeria
مقال
Keywords: جودة الخدمة; ولاء الزبائن; مؤسسة أوريدو; Service quality; customer loyalty; SERVPERF model; Ooredoo institution